Yugavīra Ācārya : śāsana prabhāvaka, Pañjāba Kesarī Ācārya Śrī Vijayavallabhasūrijī - Doshi, Fulchand H. (SAMP early 20th-century Indian books project ;, 1943)
On the life and work of Vijaya Vallabha Sūri, 1870-1954, Jaina saint.